Experimental Investigation on Motion Hydrodynamics of Water Entry for Inclined Cylinders - XIA Weixue (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
Experiments of vertical water entry for a cylinder with different inclined angles are performed at a low Froude number to investigate the cavity evolution and hydrodynamics. Unique phenomena of double cavities and separated cavity are observed. The accurate trajectories and attitude angles for the inclined cylinders are proposed, which are extracted by utilizing the method of digital image correlation from the image sequence recorded by a high-speed camera. The raw data of trajectory and attitude angle are fitted using the method of quintic smoothing spline, with which, the velocity and acceleration of the cylinders during water entry are estimated, and the cylinder characteristics of motion and hydrodynamic force are studied. The experimental results demonstrate that the unique cavity phenomena are observed for the inclined cylinder during water entry, such as cavity separation and double cavities. The acceleration increases quickly after the cylinder penetrates into water and achieves the maximum value after cavity separation occurs. After that, the acceleration decreases quickly and tends to zero. The vertical velocity of the cylinder with a large initial inclined angle decreases faster than that with a small inclined angle, while the corresponding horizontal velocity increases rapidly. The trajectories of the cylinder with different initial inclined angles generally present the characteristics of first moving in the upstream direction and then in the downstream direction. With respect to the properties of inclined angle, the angular acceleration responds very quickly to the hydrodynamic force, and it generally first increases and then decreases. In addition, the angular speed of cylinder for a large initial inclined angle increases faster than that for a small inclined angle. The inclined angle shows the same trend as well. The cylinder drag and lift coefficients rapidly increase after the cylinder enters the water, and then slowly increase after the cavity pinches off. Moreover, the force coefficients increase more quickly for the cylinder with a large initial inclined angle.